2009
DOI: 10.1197/jamia.m3111
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Decision Support Capabilities of Commercially-available Clinical Information Systems

Abstract: These findings have implications for four distinct constituencies: purchasers of clinical information systems, developers of clinical decision support, vendors of clinical information systems and certification bodies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
75
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(78 citation statements)
references
References 24 publications
1
75
0
2
Order By: Relevance
“…A survey of the CDSS capabilities of major commercial clinical information systems (CISs) in the USA found that most have small-scale, in-built functionalities -mostly comprised of alerts and reminders -with scant support for more complex decision-making tasks. 26 The reason for the emphasis on simpler functionality is clear: in order for commercial systems to be viable, they need to scale to different contexts and work environments, so providers focus on simpler tasks that are homogeneous across institutions (eg computerised order entry). The development of CDSSs to support more complex decision making (eg prediction of patient states or classifi cation of diseases) is signifi cantly more diffi cult and time consuming, and such efforts have largely remained confi ned to academic environments, where researchers have the advanced computational expertise and time required to create appropriate solutions.…”
Section: Challenges To Implementation and Adoption Of Clinical Decisimentioning
confidence: 99%
“…A survey of the CDSS capabilities of major commercial clinical information systems (CISs) in the USA found that most have small-scale, in-built functionalities -mostly comprised of alerts and reminders -with scant support for more complex decision-making tasks. 26 The reason for the emphasis on simpler functionality is clear: in order for commercial systems to be viable, they need to scale to different contexts and work environments, so providers focus on simpler tasks that are homogeneous across institutions (eg computerised order entry). The development of CDSSs to support more complex decision making (eg prediction of patient states or classifi cation of diseases) is signifi cantly more diffi cult and time consuming, and such efforts have largely remained confi ned to academic environments, where researchers have the advanced computational expertise and time required to create appropriate solutions.…”
Section: Challenges To Implementation and Adoption Of Clinical Decisimentioning
confidence: 99%
“…The lack of standard metrics for quality of service assessment impedes the evaluation and obscures the progress of technology adoption and utility. 1,5,6 From the patient's perspective, the usability and ease-of-access to technologies are obstructed by the lack of technology integration, interoperability, and standardization. For example, though telecommunication vendors and vendor resources could provide low-cost solutions as data are transmitted through their ubiquitous networks, they might also limit expansion of applications and affordability for cell phone text and data transmission for economic reasons.…”
Section: Major Barriers To Progressmentioning
confidence: 99%
“…A pervasive barrier for these endusers to secure new tools and technologies is the limited financing available for implementation, maintenance, and sustainability. [2][3][4][5][6] From the data perspective, limited access and limited data flow impede progress. Data flow into practice and hospital centers is strictly regulated, making the main data repository's (EHR=EMR systems) difficult to access and utilize for their true value with ongoing data mining and automated decision support.…”
Section: Major Barriers To Progressmentioning
confidence: 99%
“…The embedded knowledge component in a CDSS combines patient data and generates meaningful interpretations that aid clinical decision making (Liu et al, 2006). An effective CDSS also summarizes the outcomes, appraises and criticizes the caring plans, assists clinicians in ordering necessary medications or diagnostic tests, and initiates a disease management plan after a specific disease is identified (Colombet et al, 2005;Friedlin et al, 2007;Garg et al, 2005;Wadhwa, 2008;Wright et al, 2009). …”
Section: Characteristics Of Clinical Decision Support Systemsmentioning
confidence: 99%